Financial Frictions and the Great Productivity Slowdown - Duval, Romain (IMF Working Papers; Working Paper ;, 2017)
We study the role of financial frictions in explaining the sharp and persistent productivity growth slowdown in advanced economies after the 2008 global financial crisis. Using a rich cross-country, firm-level data set and exploiting quasi-experimental variation in firm-level exposure to the crisis, we find that the combination of pre-existing firm-level financial fragilities and tightening credit conditions made an important contribution to the post-crisis productivity slowdown. Specifically: (i) firms that entered the crisis with weaker balance sheets experienced decline in total factor productivity growth relative to their less vulnerable counterparts after the crisis; (ii) this decline was larger for firms located in countries where credit conditions tightened more; (iii) financially fragile firms cut back on intangible capital investment compared to more resilient firms, which is one plausible way through which financial frictions undermined productivity. All of these effects are highly persistent and quantitatively large-possibly accounting on average for about a third of the post-crisis slowdown in within-firm total factor productivity growth. Furthermore, our results are not driven by more vulnerable firms being less productive or having experienced slower productivity growth before the crisis, or differing from less vulnerable firms along other dimensions.